Shenshuaikang enema restores the intestinal barrier and microbiota-gut-kidney axis balance to alleviate chronic kidney disease via NF-κB pathway - Yan Ye; Yan Ye; Xiaopeng Huang; Xiaopeng Huang; Xiaopeng Huang; Xueying Li; Xueying Li; Fei Gao; Wenzhen Zhong; Anqi Tang; Anqi Tang; Liangbin Zhao; et al. (Frontiers in Pharmacology)
IntroductionChronic kidney disease (CKD) is a chronic progressive disease characterized by abnormalities in kidney structure or function caused by variousfactors. It has become a significant public health problem, posing a threat to human health worldwide. Shenshuaikang enema (SSKE) has demonstrated notable efficacy and safety in treating CKD, although its mechanism of action remains unclear.MethodsThe CKD rat model was induced using 2.5% adenine, and the effect of SSKE was evaluated by detecting uremic toxins, inflammatory cytokines, and renal function. The structure of the intestine and kidney was observed using electron microscopy. Pathological changes in the intestine and kidney were detected by H&E staining. The expression of Occludin, Claudin-1, and ZO-1 in the intestine was detected by immunohistochemistry. The degree of renal fibrosis was observed using Masson and PAS staining. The expression of NF-κB and MyD88 protein in the intestine, and the expression of F4/80, TLR4, NF-κB and MyD88 in the kidney were detected by immunofluorescence staining. NF-κB-RE-Luc transgenic mice were used to construct a CKD mouse model, and changes in fluorescence intensity in mice and isolated kidney tissues were detected within 1–6 days using a small animal live imager. Finally, 16S rRNA amplicon sequencing was used to monitor changes in intestinal flora in CKD patients before and after SSKE treatment.ResultsWe found that SSKE improves renal function, attenuates renal fibrosis, reduces inflammatory factor levels, and decreases damage to intestinal and renal structures in adenine-induced CKD rats. Additionally, our results suggest that SSKE regulates NF-κB pathways, increases the expression of tight junction proteins, improves intestinal permeability, promotes the growth of beneficial bacteria, inhibits the proliferation of harmful bacteria, and reduces metabolic disorders. Ultimately, these effects contribute to the efficacy of SSKE in treating CKD.ConclusionThese results indicate that SSKE restores intestinal barrier function by regulating the microbiota-gut-kidney axis, thereby treating CKD.